Changes in Alveolar Ridge Dimensions Following Immediate Implantation with and Without Buccal Gap Filling Using Cone-Beam Computed Tomography: A Clinical Trial: Immediate implantation using two methods - Sahraei, Tahereh; Semyari, Hasan; Tehranchi, Maryam; Alibakhsi, Leila (Journal of Dental School, 2024)
Objectives This study aimed to assess the changes in alveolar ridge dimensions following immediate implantation with and without buccal gap filling using cone-beam computed tomography (CBCT). Methods This prospective randomized clinical trial was conducted on 15 patients (mean age = 44.7 years) with 26 hopeless teeth. The teeth were extracted and immediately replaced with implants. The patients were randomly assigned to two test and control groups (N=13 implants each). In the test group, the gap around the implants was filled with allograft, while the control group did not receive buccal gap filling. CBCT scans were obtained at two days and four months postoperatively. The buccolingual ridge dimensions, buccal plate thickness, and buccal gap distance were measured at the implant platform and 2 and 4 mm apical to it, and changes were analyzed by the mixed-effects model (alpha = 0.05). Results In cases with a sound buccal plate having a minimum thickness of one millimeter, the alveolar ridge and buccal plate resorption were the same in the test and control groups. Conclusion: The results revealed that immediate implantation with and without buccal gap filling did not prevent alveolar ridge and buccal plate resorption